Miro proteins and their role in mitochondrial transfer in cancer and beyond - Nahacka, Zuzana; Novak, Jaromir; Zobalova, Renata; Neuzil, Jiri (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria are organelles essential for tumor cell proliferation and metastasis. Although their main cellular function, generation of energy in the form of ATP is dispensable for cancer cells, their capability to drive their adaptation to stress originating from tumor microenvironment makes them a plausible therapeutic target. Recent research has revealed that cancer cells with damaged oxidative phosphorylation import healthy (functional) mitochondria from surrounding stromal cells to drive pyrimidine synthesis and cell proliferation. Furthermore, it has been shown that energetically competent mitochondria are fundamental for tumor cell migration, invasion and metastasis. The spatial positioning and transport of mitochondria involves Miro proteins from a subfamily of small GTPases, localized in outer mitochondrial membrane. Miro proteins are involved in the structure of the MICOS complex, connecting outer and inner-mitochondrial membrane; in mitochondria-ER communication; Ca2+ metabolism; and in the recycling of damaged organelles via mitophagy. The most important role of Miro is regulation of mitochondrial movement and distribution within (and between) cells, acting as an adaptor linking organelles to cytoskeleton-associated motor proteins. In this review, we discuss the function of Miro proteins in various modes of intercellular mitochondrial transfer, emphasizing the structure and dynamics of tunneling nanotubes, the most common transfer modality. We summarize the evidence for and propose possible roles of Miro proteins in nanotube-mediated transfer as well as in cancer cell migration and metastasis, both processes being tightly connected to cytoskeleton-driven mitochondrial movement and positioning.